PENGETAHUAN DAN PERAN SUAMI SEBAGAI AYAH TENTANG INISIASI MENYUSUI DINI (IMD) DAN KEBERHASILAN ASI EKSKLUSIF PADA BAYI 0 â 6 BULAN DI DESA RAKNAMO KECAMATAN AM ABI OEFETO KABUPATEN KUPANGTAHUN 2011 - AWANG, MARIANA NGUNDJU (JURUSAN KEBIDANAN POLTEKKES KUPANG, 2014)
Background, One of health problem in the East NusaTenggara is infant mortality rate and malnutrition are still high. The key is because mothers behavior. Infants should be have a breast milk exclusively for six months during that months babies should not get any food and only drink a breastmilk from their mother. Ideally babies get breastfeed for two years. Giving the exkusive breastfeeding is difficult to achieve it if not accompanied by husband conciousness. The husband should not get their wife into the crop when they babies was six month old yet. Thus baby can get breastfeeding and malnutrition can be pressed. In East Nusa Tenggara province prevalence of infant malnutrition reached 9,4 percent or higher than national rate that only 5,4 percent. The Successfull of breastfeeding very determined by involvement of her husband from the pregnancy until the delivery and evend during lactation. Breastfeeding is a family activity, the success of breastfeeding without father understanding of breastfeeding is 26.9 percent and the 98.1 percent breastfeeding understanding group (pediatric Cinical, 1994). Role of the father for the succesfull of breastfeeding is very huge, therefore it is necessary to provide breastfeeding education for fathers and families when antenatal care.The objective of this research is knowing knowledge and role of husband for breastfeeding succesfull in village of Amabi Oefeto, Raknamo District Of year 2011Result: There was an increase in the knowledge og husband after giving information about early initiation of breastfeeding and exclusive breastfeeding reach 77,2 percent. Husband wifes role in helping to deliver milk to the baby after giving information and a demonstration there is an increase of 22.9 percent to 85.7 percent in the last observation. Kruskal-Wallis statistical test results on each observation from the first, second and third at 0.65, 0:13 and 0, meaning 0,00 it mean that husbands role can be increased along with the increase of knowledge and its role as the father of the early initiation of breastfeeding and the importance of exclusive breastfeeding for infants.Conclusion: there is an increase of husband knowledge about early initiation of breastfeeding and exclusive breastfeeding after giving information and a significant increase of the role of the husband as the father on the successfull of the early initiation of breastfeeding and exclusive breastfeeding after demonstration.